Management Of Phylantrophic Funds In People's Economic Development - Khikmah, Nurul; Mujib, Abdul; Khasanah, Karimatul (Sunan Kalijaga: Islamic Economics Journal, 2022)
The purpose of this paper is to learn more about ZISWAF's management. With a phenomenological approach, this research method uses a qualitative approach to describe the findings between facts and reality that exist in society. While data collection requires literature and documentation investigations, so that it is recognized that the ZISWAF Fund can be maximized for the people's economic development, however the fund is currently primarily engaged in social service activities, charitable help, orphan compensation, Madrasah development, and other similar activities. They even tend to overlook other Muslims' interests, such as legal aid, In addition to efforts to discover the potential of philanthropy, child protection, public policy advocacy, women's empowerment, and several other key goals still require assistance from the use of philanthropic money and its impact on people's economic development, particularly the poor and underprivileged.